Variability, coherence and forcing mechanisms in the New Zealand ocean boundary currents. (July 2018) - Fernandez, Denise; Bowen, Melissa; Sutton, Philip
Highlights: This study analyses the variability of all the New Zealand currents simultaneously. There is no evidence of trends in the transports of the New Zealand currents. The currents have shown little correlation with each other and with winds. Abstract: Several fast, narrow boundary currents flow along the eastern margin of New Zealand forming part of the western boundary current system of the South Pacific. In this study, using over 20 years of satellite altimeter observations and in situ data, we investigate the mean and variability of the current transports at seasonal, interannual and decadal time scales. We relate the means and fluctuations of the currents to the Southern Oscillation Index and to potential drivers of the circulation, including local and basin-scale winds. We also investigate the barotropic and baroclinic responses of the currents to basin-scale wind forcing using Rossby wave models. We find the currents are highly variable and there are no discernible trends in the transports since 1993. There is little coherence between transports along the boundary, suggesting a range of mechanisms drive the variability of the currents individually rather than the system as a whole. There is little correspondence between transports in any of the boundary currents and the El Niño/Southern Oscillation. We also find that the transports are not well described by the arrival of linear Rossby waves. At decadal time scales, only transports in the Subantarctic Front show a close correspondence with the variability of the wind stress curl averaged over the South Pacific. Seasonality is significant in two of the currents, likely driven by seasonality in local winds. In contrast with the larger East Australian Current, which forms part of the same South Pacific western boundary current system, we see collectively little evidence of a link between trends and variability in the New Zealand boundary currents and large-scale or local wind forcing.